Frequency Analysis of Rainfall Data - Gupta, S. K.; Dalal, S. S.; Babu, Ram (Indian Forester, 1968)
Rainfall is the most important component of the hydrological cycle. Rainfall data is needed by all agencies dealing with the use and management of natural resources. The total rainfall and distribution, intensity, duration and frequency are often needed for design of engineering structures, analysis of erosion and flood problems. The annual and seasonal data are usually represented by bar diagrams. These do not give much useful information. Probability and frequency analysis of rainfall data will be more useful. The paper describes the method of frequency analysis of annual, seasonal, monthly and daily rainfall data and also for duration less than 24 hour. Similar analysis for other localities as recommended for preparing an isopluvial map of India for various duration and recurrence intervals.